Monitoramento de poluição atmosférica através de método biológico com utilização de liquens, no município de Caçapava do Sul (RS) - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The worsening of atmospheric pollution and the consequent decline in air quality necessitate the development of practical, accessible, and rapid monitoring methods, particularly in areas prone to potential contamination sources such as mining and urban environments. Among these approaches, bioindicators like lichens stand out due to their high sensitivity to various toxic pollutants. Lichen biomonitoring offers advantages such as relatively low cost, efficiency in large-scale research, and the ability to detect pollutants at low concentrations. Mining activities, such as limestone extraction, contribute to atmospheric contamination through the release of fine particles and sulfur dioxide emissions, making lichens effective tools for monitoring such impacts. This study aimed to use lichen species diversity as a bioindicator of air quality in the municipality of Caçapava do Sul, Brazil. Monitoring was conducted at eight points, encompassing areas near mining activities and control points in the Parque Natural Municipal da Pedra do Segredo. The qualitative-quantitative analysis included lichen biodiversity and the occupied area of species, measured using a reticulum and pixel-counting software. These methods enabled the calculation of the Air Purity Index (IPA) and lichen coverage (%) concerning pollution sources. The results revealed that sites near mining areas exhibited a predominance of crustose genera, such as Cryptothecia sp., which are more resistant to pollution, reflecting severe environmental contamination associated with low IPA values (0.83) and lichen coverage (1.62%). Conversely, the most distant sites (13,200 m) showed greater diversity of foliose and fruticose genera, such as Parmotrema sp. and Coccocarpia sp., corresponding to more preserved environmental conditions, with IPA values of 15.78 and lichen coverage of 31.73%. Pearson's linear correlation indicated a very strong positive relationship between distance and environmental indicators (r=0.98 for IPA and r=0.95 for lichen coverage), demonstrating that environmental impact significantly decreases with increasing distance from the emission source. These results underscore the effectiveness of lichens as bioindicators and contribute to understanding the impacts of mining activities on air quality and lichen biodiversity.
Keywords: Bioindicador; Poluição atmosférica; Liquens; Bioindicator; Air pollution; Lichens; CNPQ::ENGENHARIAS